Effective Use of Emamectin Benzoate for the Management of Spodoptera frugiperda (J. E. Smith) in Maize - Rampelotti-Ferreira, Fátima T.; Thiesen, Leonardo V.; Corassa, Janaina de N.; Nardon, Adriana; Santos, Leandro V. dos; Rosa, Daniel; Pitta, Rafael M. (BioAssay, 2021)
Emamectin benzoate has been largely used for controling lepidopterans larvae in grains and fiber crops and, therefore, selection of resistant populations to this pesticide is a real risk if ignored the insect resistance management (IRM) strategies. We studied the susceptibility of Spodoptera frugiperda (Smith, 1797) populations in the state of Mato Grosso - Brazil to Emamectin benzoate as well as a field study about Mode of Action rotation including this compound. Low variations in susceptibility (resistance ratios, 1,01-7,31 fold) were detected among the evalueted S. frugiperda populations. The field study reinforced our monitorings outcome that Emamectin Benzoate controls S. frugiperda and its use in IRM in Mato Grosso is practicable. Susceptibility monitoring should be continuous in order to detect possible increases of tolerance rates not only for this pesticide but also for all compounds used for this pest management aiming to apply early mitigation actions.